Ward, Henry Charles (audio interview #1 of 1) - Ward, Henry Charles (1909 - 7/3/2002); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - Ward was interviewed in the interviewer's office at CSULB. 1/5/1982